Canstatin represses glioma growth by inhibiting formation of VM-like structures - Ma Yuqiang (De Gruyter, 2021)
Vasculogenic mimicry (VM) is different from classical tumor angiogenesis and does not depend on endothelial cells. VM is closely related to the prognosis of various cancers. Canstatin was first identified as an endogenous angiogenesis inhibitor. In the present study, the inhibitory effect of canstatin on VM formation was evaluated. Human glioblastoma cell lines U87 and U251 were letivirally transduced to overexpress canstatin gene or GFP as control. In vitro assays showed that canstatin overexpression reduced the tube formation of U87 and U251 cells in Matrigel. A xenograft glioma model was created by subcutaneous injection of lentivirally modified U87 cells into nude mice. The results of in vivo experiments showed that canstatin gene introduction inhibited the growth of glioma xenografts. In tumor xenografts overexpressing canstatin, U87-mediated formation of VM-like structures and VM-related VEGF (vascular endothelial growth factor) expression were remarkably reduced. Canstatin overexpression also decreased the phosphorylation of Akt and reduced the expression of Survivin in vitro. In addition, HIF-1α production and MMP-2 secretion were decreased by canstatin overexpression. Therefore, these results suggested a protective role of canstatin during VM-like structure formation of glioma probably via inhibiting signaling pathways inducing vasculogenic mimicry.